A systematic review of empirical studies incorporating English movies as pedagogic aids in English language classroom - Pavithra, K.; Gandhimathi, S. N. S. (Frontiers in Education, 2024)
The use of movie as an audio-visual multimodal tool has been extensively researched, and the studies prove that they play a vital role in enhancing communicative competence. Incorporating authentic materials like movies, television series, podcasts, social media, etc. into language learning serves as a valuable resource for the learners, for it exposes them to both official and vernacular language. The current study aims to systematically analyse the preceding studies that conjoined English movies into the curriculum to teach English. It also examines and evaluates the empirical research that various researchers conducted from 2000 to 2023. The articles were primarily sourced from prominent academic databases such as ProQuest, ScienceDirect, Scopus, Web of Science, and Google Scholar. Inclusion and exclusion criteria were applied in screening the 921 sources, of which 23 empirical studies were eligible for the review as a result of a three-stage data extraction process as shown in the "Preferred Reporting Items for Systematic Reviews and Meta Analyses" (PRISMA) chart. The extraction of data from the review encompasses an overview of the empirical studies, methodologies, participants, and interventions. The extracts were systematically analysed using the software's End Note and Covidence. The analysis of the existing literature and experimental data substantiates that teaching and learning English as a second or foreign language using movies as teaching aids exhibit promising prospects for enhancing English language proficiency. The findings of the study reveal different genres of movies that aid the facilitator in producing effective instruction materials with clearly defined objectives and guided activities. It is also observed that the learners have a positive experience with long-term learning benefits.